Teamwork quality and team performance of the national railways transport company (SNTF) in Algeria - Elamine, Boussam Mohamed (2015)
The research filled a gap on the effect of teamwork quality on team performance in the Algerian national railways SNTF. Random sampling was used to select respondents for a survey from among members of SNTF teams in Algeria firms with total respondents 113 teams. Under many team PLS-SEM was used to analyse the relationships between teamwork quality, team performance while path coefficient and assessment of measurement and structural model used to test the research hypotheses. Findings indicate that two out of seven teamwork quality factors had significant effects namely the communication and cohesion on team performance but not the balance of member contribution, mutual support, effort and cohesion and improvisation. The findings suggest that managers are required to be concerned about how to improve team effectiveness in order to assess higher team performance. This should facilitate an environment conducive to teamwork to realize superior course of reflective activities. The study also provides a theoretical implication of the study are also highlighted.